The environmental impacts of solid waste disposal and environmental management in the municipality of Iranduba - AM (Research, Society and Development, 2023)
In Brazil, the PNRS was sanctioned, which designates solid waste management as a shared responsibility between the government, the population, and companies. The objective of the present research was to evaluate the possible impacts caused by the incorrect disposal of waste in Iranduba/AM, in addition to the characterization of the collected trash and, above all, to generate an overview of the socioeconomic and socio-environmental perception of workers linked to the Association of Recyclable Materials Collectors of Iranduba - New Hope. The methodology has a descriptive-exploratory character based on the research of qualitative and quantitative data, in addition to the georeferencing of the waste collection areas. To analyze the socio-environmental perspective of the collectors, leaders, or managers of the association, the Iramuteq software was used. Descriptive statistics were used to interpret the socioeconomic profile of the associates. In addition, the characterization of waste collected by the association was based on Law 12,350 of 2010. The diagnosis of possible impacts resulting from the disposal of trash to the environment was based on the matrix model of Leopold (1971), modified by Santos (2004) and Sobral et al. (2007). Analyzing the context of Iranduba, it was possible to observe that despite the provisions, goals, and instruments imposed by the PNRS of 2010 and the extensions of the deadlines for the establishment of sound environmental management practices, the municipality still does not present the effectiveness of a municipal management plan to waste, which contributes to the environmental impacts at the study site. Furthermore, the Nova Esperança association promotes ecological awareness among the local population. It performs essential work for the management of solid waste in the city, even without the support of the city hall.